2007
DOI: 10.1017/s0317167100006041
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Versus Microsurgical Resection of Third Ventricle Colloid Cysts

Abstract: Colloid cysts of the third ventricle represent about 0.5-2 percent of intracranial tumors.1,2 Although uncommon, they are an important clinical entity because of their ability to cause cerebrospinal fluid (CSF) obstruction and sudden death. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In one population-based study, one third of patients with symptomatic colloid cysts presented with acute neurological deterioration, underscoring the need for their treatment. There has been some debate over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 58 publications
4
65
0
Order By: Relevance
“…1,11 Open surgery is traditionally considered the gold standard for the treatment of third ventricle colloid cysts, with many authors having reported a residual/recurrence rate ranging from 0% to 1.1% when using a transcallosal or transfrontal-transventricular approach. 5,6,8,10,13,18,19,26 How ever, these approaches have high operative morbidity and mortality rates because they are potentially associated with disabling complications such as venous infarction, hemiparesis, memory deficit, subdural hematoma, meningitis, and ventriculitis. 5,6,13,19,26 Taking these results into consideration, alternative options for the treatment of these lesions were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…1,11 Open surgery is traditionally considered the gold standard for the treatment of third ventricle colloid cysts, with many authors having reported a residual/recurrence rate ranging from 0% to 1.1% when using a transcallosal or transfrontal-transventricular approach. 5,6,8,10,13,18,19,26 How ever, these approaches have high operative morbidity and mortality rates because they are potentially associated with disabling complications such as venous infarction, hemiparesis, memory deficit, subdural hematoma, meningitis, and ventriculitis. 5,6,13,19,26 Taking these results into consideration, alternative options for the treatment of these lesions were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…108 Although uncommon, they are an important clinical entity because of their ability to cause CSF obstruction at the foramina of Munro with resultant hydrocephalus, which in the acute state can lead to sudden death. 108 If the obstruction of the foramina of Monro is asymmetrical, one lateral ventricle can grow larger than the other, resulting in bowing of the septum pellucidum to the nonaffected side. 109 Although microsurgery has been the classic treatment option, 110 the composition and location of these cysts make them ideally suited for endoscopic excision.…”
Section: Colloid Cystsmentioning
confidence: 99%
“…We have previously presented our data in comparison to microsurgical resections, showing that endoscopic resection of colloid cysts can be performed with a significantly lower risk of complications than microsurgical resection (4% vs 33%), and with equivalent surgical success. 108 In addition, operative time and length of hospital stay are both significantly reduced with endoscopic resection. Similar results were found in a series of 30 patients reported by Lewis et al, 116 where half underwent open resection and the other half endoscopic resection of a colloid cyst.…”
Section: Colloid Cystsmentioning
confidence: 99%
“…Colloid cyst endoscopic surgery is described widely in the literature and is becoming a popular surgical technique in the management of these lesions (Grondin et al, 2007;Horn et al, 2007;. Navigation assisted endoscopy may be needed in some of these patients, especially when there is no accompanying hydrocephalus (Souweidane 2005).…”
Section: Endoscopic Management Of Intra-ventricular Lesionsmentioning
confidence: 99%